Implementation Extreme Programming in Development Application Management Shop Based Android - Deni Sanjaya; Sri Wahyuni; Nadia Rista (Jurnal Pengetahuan dan Pendidikan, 2025)
Feri Elektronik Store still conducts its operational activities using conventional methods, particularly in recording product data and sales transactions, which leads to several issues such as slow data retrieval, risk of data loss, and low efficiency and accuracy in inventory management. This study aims to design and develop an Android-based store management application to improve the effectiveness of store operations. The system was developed using the Extreme Programming (XP) methodology, which consists of planning, design, coding, and testing phases. Data collection techniques included observation, literature study, and interviews. The application was developed using Kotlin in Android Studio with Firebase Realtime Database as the database system and is equipped with a QR Code scanning feature to accelerate product identification and transaction processes. The results indicate that the developed application is user-friendly, provides an informative interface, and effectively supports inventory management, sales transactions, and real-time reporting in an accurate and structured manner. The implementation of Extreme Programming enables an adaptive development process that meets user requirements and significantly enhances operational efficiency at Feri Elektronik Store